POLA KOMUNIKASI BUDAYA PADA PERNIKAHAN ADAT DI NEGERI OHOI OHOIRENAN, KABUPATEN MALUKU TENGGARA - Alex Robert Tutuhatunewa; Jimmy Sirait; Eunike Ubra (Fakultas Ilmu Sosial dan Ilmu Politik, 2023)
In cultural diversity, the process of social interaction and communication often encounters problems or obstacles that were not previously expected. For example, in the use of language, symbols, community values or norms and so on. At the level of indigenous communities in Indonesia, communication and culture are things that cannot be separated. Communication and culture have a reciprocal relationship, like two sides of a coin. Culture is part of communication behavior and in turn communication also determines, maintains, develops or passes on culture. The type of research used in this study is descriptive qualitative. According to the qualitative research method, it is a synthesis of systematic, clear, comprehensive literature studies by identifying, analyzing, evaluating through collecting existing data with an explicit search method and involving a critical review process in selecting studies. The results of this research 1 Traditional marriages in Ohoi Ohoirenan Country have so far not been optimal. This can be seen in the internalization of cultural transmission. Traditional marriage is a very important form of cultural reflection for the Kei people. Traditional marriages from one generation to another tend to ignore the cultural values themselves, quite a few of the younger generation and parents preserve traditional marriage culture. This is caused by many assumptions, even if there are those who still use traditional wedding culture as a culture that is preserved, but its implementation will definitely experience errors and a lack of understanding of the culture itself. 2Society's response, in this case the younger generation, in communication patterns and traditional marriage culture in Ohoi Ohoirenan Country, in a society there are also individuals who experience various obstacles in the internalization process, communication patterns, socialization and acculturation, which causes the results to be less good. Likewise with Ohoi Ohoirenan Country, the results of interviews show that the younger generation does not clearly know about traditional marriage and in its implementation they do not take the initiative to find out the details of traditional marriage culture. 3 Based on the results of interviews conducted by the author with the informants obtained. So the researcher describes the results of interviews, namely the head of the state government, traditional elders (tenyanan), young people and couples as informants, enough to provide an overview of the extent of the communication patterns of marriage culture in the Ohoi Ohoirenan State, Southeast Maluku Regency in social change in society. The Ohoi Ohoirenan State Government stated that traditional marriages in recent years have not gone well. Due to lack of awareness among the country's children.